Analisis Efektifitas Pendayagunaan Zakat Produktif Pada Pemberdayaan Mustahik (Studi Kasus LAZISMu Pusat) - Syahrul Amsari (Faculty of Islamic Religion, Universitas Muhammadiyah Sumatera Utara, 2019)
This research aims to determine how the pattern of utilization of zakat productively applied in LAZISMu which then also the model applied in the empowerment mustahik so it is unknown whether the revenue mustahik after getting zakat productive of LAZISMu there is an increase or a change both in terms of revenue, business ethics and ability to pay ZIS. LAZISMu in conducting productive utilization of zakat through economic programs that aims to create entrepreneurs and provide new jobs for people who do not have jobs. The method used is qualitative method is to analyze and describe the results of the data obtained in the form of words. The results showed that of the indicators of empowerment mustahik, the impact of empowerment mustahik Development program Economy Family Amanah is, as many as 14 people mustahik of 14 respondents were powerless in terms of increased revenue, 14 mustahik of 14 respondents powerless in terms of the implementation of business ethics of Islam, and 14 mustahik person from 14 respondents helpless terms ZIS payment of these results can be drawn that the ZIS has been effective in empowering mustahik. In the productive utilization of zakat, LAZISMu besides channeling done alone then also always optimize assemblies, institutions and Ortom in Muhammadiyah so that a broader impact beneficiaries and programs more varied.